Sulfasalazine induced atypical drug reaction with eosinophilia and systemic symptoms syndrome: a case report - Shravani, Etrouth (International Journal of Basic & Clinical Pharmacology, 2022)
Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a type IV b hypersensitivity reaction characterized by cutaneous manifestations, fever, lymphadenopathy, hematologic abnormalities, and multiple organ manifestations. We report a case of sulfasalazine induced DRESS syndrome who was admitted with a complaint of morbilliform rash all over the body, a fever of 100oF, and severe abdominal pain. Initially the patient did not mention about intake of sulfasalazine while taking the drug history as he could not remember the past medication. The laboratory investigations revealed elevated eosinophils, WBC, and liver function tests. The patient was treated with antibiotics assuming tropical infection, but the patient’s condition was not improving. Later while taking proper drug history from a patient representative over the telephone revealed that the patient was in 4th week of tablet sulfasalazine 500 mg treatment for polyarthritis. Further, the J-SCAR scale was used to diagnose it as Sulfasalazine induced atypical DRESS syndrome. The patient was treated with topical and intravenous corticosteroids and antihistamine; the patient exhibited surprising symptomatic improvement. The patient was given a tapering dose of oral corticosteroid tablet prednisolone 20 mg for three weeks and topical corticosteroid mometasone lotion for two weeks upon discharge.